2017
DOI: 10.1007/s00253-017-8158-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrin beta and receptor for activated protein kinase C are involved in the cell entry of Bombyx mori cypovirus

Abstract: Receptor-mediated endocytosis using a β1 integrin-dependent internalization was considered as the primary mechanism for the initiation of mammalian reovirus infection. Bombyx mori cypovirus (BmCPV) is a member of Reoviridae family which mainly infects the midgut epithelium of silkworm; the cell entry of BmCPV is poorly explored. In this study, co-immunoprecipitation (Co-IP), virus overlay protein binding assay (VOPBA), and BmCPV-protein interaction on the polyvinylidene difluoride membrane (BmCPV-PI-PVDF) meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…JQ824201.1) and clathrin heavy chain (clathrin, GenBank accession No. NM_001142971.1) proteins that were interacting proteins of BmCPV were chosen 23 and the effects of silencing these genes on the infectivity of BmCPV in BmN cells were investigated. Quantitative reverse transcription–polymerase chain reaction (RT-qPCR) results showed that AP-315 and clathrin-348 were specific small interfering RNAs (siRNAs) for the AP-1 and clathrin genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…JQ824201.1) and clathrin heavy chain (clathrin, GenBank accession No. NM_001142971.1) proteins that were interacting proteins of BmCPV were chosen 23 and the effects of silencing these genes on the infectivity of BmCPV in BmN cells were investigated. Quantitative reverse transcription–polymerase chain reaction (RT-qPCR) results showed that AP-315 and clathrin-348 were specific small interfering RNAs (siRNAs) for the AP-1 and clathrin genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It suggests that VP5 sequesters RACK1 and VDAC2 in the apoptosis-inducing process 21 . Furthermore, together with integrin beta, RACK1 is involved in the cell entry of Bombyx mori cypovirus 22 . Additionally, RACK1 was discovered as one of the 16 interacting cellular proteins by the yeast two-hybrid system during a screen for classic swine fever virus (CSFV) NS5A interactive proteins in the cDNA library of the swine umbilical vein endothelial cell (SUVEC) 23 .…”
Section: Introductionmentioning
confidence: 99%
“…(3) Autophagy is only slightly induced by BmCPV infection, and could not prevent the invasion and replication of the virus 11 . (4) Establishing a BmCPV infection depends on other factors interacting with integrin beta and receptor for activated protein kinase C (RACK1) to form a receptor complex for the entry of BmCPV 12 . Thus far, the molecular mechanism underlying the midgut infection of BmCPV and the antivirus immune response to BmCPV infection is not clearly understood due to the complexity in dsRNA virus infection.…”
Section: Introductionmentioning
confidence: 99%